Health Education STUNTGUARDS: Stunting Prevention through Understanding Nutrition and Impact of Early Marriage on Teenagers - Lukman, Mamat; Yamin, Ahmad; Mulya, Adelse Prima (Media Karya Kesehatan, 2024)
WHO states that Indonesia is ranked 5th in the world for the highest prevalence of stunting, and one of the provinces that contributes to the highest number of stunting cases is West Java. Problems that occur in teenagers related to reproductive health are one of the factors in Indonesia's high stunting rate. Stunting prevention can be done by reducing the number of risk factors, one of which is by providing health education to teenagers. This community service aims to increase teenagers' knowledge regarding stunting through health education related to understanding nutrition and the impact of early marriage on teenagers. The activities were interactive lectures using media like power points, leaflets and posters. The sample from this research was representative of class X and XI children at SMAN 1 Baleendah. Wilcoxon test showed p<0,05. It was found that there was an increase in teenagers' knowledge before and after health education was carried out. From these results, it can be concluded that implementing the "STUNTGUARDS" activity at SMA Negeri 1 Baleendah increased students' knowledge about stunting, balanced nutrition, and early marriage as risk factors for stunting. The use of the lecture method accompanied by existing audio-visual media helps teenagers to be able to capture information easily. So that teenagers' knowledge can increase significantly.Keywords: Early marriage, stunting, health education, nutrition, adolescent, stuntguards.